Diagnostic Tips from a Video Series and Literature Review of Patients with Late-Onset Tay-Sachs Disease. Issue 1 (27th December 2022) - Riboldi, Giulietta Maria; Lau, Heather
Background: Late-Onset Tay-Sachs (LOTS) disease is a rare, progressive neurological condition that can dramatically affect the life of these patients. The diagnosis of LOTS is easily missed because of the multifaced presentation of these patients, who can initially be assessed by neuromuscular or movement disorder specialists, or psychiatrists. Clinical trials are now becoming available for LOTS. Therefore, early diagnosis can be detrimental for these patients and for insuring informative research outcomes. Methods: We characterized a cohort of nine patients with LOTS through a detailed clinical and video description. We then reviewed the available literature regarding the clinical description of patients with LOTS. Our findings were summarized based on the predominant phenotype of presentation to highlight diagnostic clues to guide the diagnosis of LOTS for different neurology specialists (neuromuscular, movement disorders) and psychiatrist. Results: We described a cohort of 9 new patients with LOTS seen at our clinic. Our literature review identified 76 patients mainly presenting with a neuromuscular, cerebellar, psychiatric, stuttering, or movement disorder phenotype. Diagnostic tips, such as the triceps sign, distinct speech patterns, early psychiatric presentation and impulsivity, as well as neurological symptoms (cerebellar or neuromuscular) in patients with a prominent psychiatric presentation, are described. Discussion: Specific diagnostics clues can help neurologists and psychiatrists in the early diagnosis of LOTS disease. Our work also represent the first video presentation of a cohort of patients with LOTS that can help different specialists to familiarize with these features and improve diagnostic outcomes. Highlights: Late-Onset Tay-Sachs (LOTS) disease, a severe progressive neurological condition, has multifaced presentations causing diagnostic delays that can significantly affect research outcomes now that clinical trials are available. We highlight useful diagnostic clues from our cohort (including the first video representation of a LOTS cohort) and comprehensive literature review.